FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS KOMITE AUDIT - Riyantini Amalia Paramitha; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the factors influencing the audit committee quality. The analysis used independent variable of board of commissioner characteristics, the existence of a big four auditor, managerial ownership, company size, and the company’s leverage. The dependent variable is audit committee quality. The sample used is secondary data from the Indonesia Stock Exchange (IDX) is a company's annual report in 2011. Samples were taken at random from the 356 non-financial companies. Seventy-eight non-financial companies designated as the calculation formula Babbie. Variable characteristics of the board of commissioners, the presence of big four accounting firm, managerial ownership, firm size and leverage were analyzed using multiple linear regression, with hypothesis testing of  t statistic and F statistic.The results of this research indicate that leverage is significantly positive influence the quality of the audit committee. While the characteristics of the board of commissioners, the presence of big four accounting firm, managerial ownership and firm size does not have a significant influence on the quality of the audit committee.